On the influence of geometrical parameters and erosive wear on the dynamic behaviour of Pelton turbine runners - Maxime Chiarelli; David F. Vetsch; Robert M. Boes; Loïc Andolfatto; Cécile Münch-Alligné (Results in Engineering)
Hydro-abrasive erosion and material fatigue are amongst the main challenges for Pelton turbines. Erosive wear caused by sediment-laden water, significantly impacts turbine efficiency, time between overhaul and service life. While surface coatings and operational adjustments, like shutdowns during high sediment concentration events, offer some mitigation, damage assessment still relies on visual inspections and associated downtime. This study aims to understand the dynamic behaviour of a prototype Pelton runner by examining the influence of boundary conditions as well as the hub and bucket designs on the runner's vibration modes. Additionally, four erosion scenarios are investigated through numerical modal simulations on a single bucket geometry, by removing material from specific erosion-affected locations. The results indicate a weak correlation between main splitter erosion and frequency shifts for all modes. The most realistic erosion scenario, which includes the erosion of a large surface in the bucket intrados, reveals the balanced effect of mass loss and stiffness reduction resulting from material removal. Consequently, most vibration modes remain unaffected by this realistic scenario, except two modes which show significant frequency shifts. These findings enhance the understanding of the dynamic behaviour of Pelton turbines. Moreover, understanding the impact of common wear on Pelton runners is crucial for developing advanced vibration-based monitoring tools that would enhance turbine safety and minimize downtime.